2011
DOI: 10.1103/physrevlett.107.233201
|View full text |Cite
|
Sign up to set email alerts
|

Universal Three-Body Physics for Fermionic Dipoles

Abstract: A study of the universal physics for three oriented fermionic dipoles in the hyperspherical adiabatic representation predicts a single long-lived three-dipole state, which exists in only one three-body symmetry, should form near a two-dipole resonance. Our analysis reveals the spatial configuration of the universal state, and the scaling of its binding energy and lifetime with the strength of the dipolar interaction. In addition, three-body recombination of fermionic dipoles is found to be important even at ul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…(39) is the right side of the adiabatic relation in Eq. (34). This completes the derivation of the inelastic two-atom loss rate in Eq.…”
Section: Inelastic Two-atom Loss Ratesupporting
confidence: 64%
See 2 more Smart Citations
“…(39) is the right side of the adiabatic relation in Eq. (34). This completes the derivation of the inelastic two-atom loss rate in Eq.…”
Section: Inelastic Two-atom Loss Ratesupporting
confidence: 64%
“…This identification can be verified by using the adiabatic relation in Eq. (34). The only dependence of the Hamiltonian on the scattering length a is in the interaction term in the Hamiltonian density H int in Eq.…”
Section: Inelastic Two-atom Loss Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The methods for treating few-body problems as well as fundamental aspects of Efimov physics and its experimental observations are discussed in Section 3. Moreover, although the Efimov effect does not occur for three-body systems composed of three identical fermions, Wang et al (2011e) have shown the existence of a new kind of universal state for three fermionic dipoles. For instance,the recent push to create ultracold dipolar gases-whether from ground state molecules Ospelkaus et al, 2008;Deiglmayr et al, 2008) where the permanent dipole moment is extremely large or from atoms with large magnetic dipolar moments like Cr, Dy, and Er (Giovanazzi et al, 2002a;Lu et al, 2011Lu et al, , 2012Aikawa et al, 2012)-has opened avenues for exploring few-body systems where the interactions are now anisotropic and have a longer-range character than for neutral atoms or nuclear systems (Lahaye et al, 2009;Jin and Ye, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Anisotropic interactions inherent in ultracold dipolar gases are sources of various exotic phenomena, which has attracted numerous investigations from different perspectives, including those in few-body physics [1][2][3][4], ultracold chemistry [5][6][7], many-body physics [8][9][10][11][12][13][14] and quantum computation [15][16][17]. The recent work on ultracold collisions of highly magnetic atoms like lanthanides has shown a very dense spectrum of Fano-Feshbach resonances [18][19][20].…”
mentioning
confidence: 99%